Fighting crime through crime analysis: The experience of using innovative technologies in European Union countries: La lucha contra la delincuencia mediante el análisis de la delincuencia: la experiencia del uso de tecnologías innovadoras en los países de la Unión Europea - Kalynovskyi , Oleksandr; Shemchuk, Viktor; Huzela, Mykhailo; Predmestnikov, Oleh; Zharovska, Halyna (Political Questions, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*110.55px); top: calc(var(–scale-factor)*261.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14044);" role="presentation">The aim of this article was to study innovative technologies <span dir="ltr" style="left: calc(var(–scale-factor)*96.38px); top: calc(var(–scale-factor)*272.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08833);" role="presentation">and tools in the context of the introduction of crime analysis tools <span dir="ltr" style="left: calc(var(–scale-factor)*96.38px); top: calc(var(–scale-factor)*283.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09201);" role="presentation">used in the countries of the European Union EU, to the Ukrainian <span dir="ltr" style="left: calc(var(–scale-factor)*96.38px); top: calc(var(–scale-factor)*294.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09656);" role="presentation">practice. The research involved the following methods: statistical <span dir="ltr" style="left: calc(var(–scale-factor)*96.38px); top: calc(var(–scale-factor)*305.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.10012);" role="presentation">analysis, induction and deduction, classification and comparison. <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*316.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1233);" role="presentation">The study described the legally enshrined powers of the Ukrainian police <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*327.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12217);" role="presentation">with respect to information and analytical activities. Current trends in the <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*338.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.11452);" role="presentation">number of criminal offenses committed in Ukraine under separate articles <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*349.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.17124);" role="presentation">were determined, and these trends were compared before and after the <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*360.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05424);" role="presentation">adoption of the Law of Ukraine “On National Police”. The introduction of the <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*371.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1116);" role="presentation">latest means of criminal analysis into Ukrainian practice was also studied. <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*382.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08813);" role="presentation">The conclusions established that the technologies used by EU countries can <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*393.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.07905);" role="presentation">increase the effectiveness of law enforcement agencies in Ukraine, provided <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*404.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14219);" role="presentation">that certain adaptation measures are implemented. Moreover, the results <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*415.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1266);" role="presentation">obtained during the research can be used by law enforcement agencies to <span dir="ltr" style="left: calc(var(–scale-factor)*53.86px); top: calc(var(–scale-factor)*426.43px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09683);" role="presentation">improve and optimize crime analysis.